(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Degenerative diseases, such as Alzheimer’s, Parkinson’s, diabetes, and cardiovascular disease, are global health problems with increasing prevalence and economic burden. This study aims to analyse the role of Artificial Intelligence (AI) in accelerating the drug discovery process, particularly in the development of targeted therapies for degenerative diseases. The research method used is a systematic literature review of national and international journal articles published between 2019 and 2024. The data were analysed qualitatively by examining the contribution of AI at various stages of drug discovery. The results of the study show that AI plays a significant role in molecular target identification, virtual screening, drug repurposing, and drug candidate optimisation, with a prediction accuracy rate ranging from 70–85%. The application of AI is reported to reduce drug discovery time by approximately 50% and development costs by up to 40%. The conclusions of this study confirm that AI is a strategic tool in modern pharmaceutical biotechnology development, although its implementation still requires further experimental validation, standardisation, and adequate data availability, particularly in the context of drug development in Indonesia